ARNI Versus Perindopril for Remodeling in HFrEF. A Cohort Study - Noor Muhammad Azlan Shah Bin Atan MBBS; Mohd Firdaus Bin Hadi MBBS; Victoria Wen Yeng Teoh; Mahmoud Danaee PhD; Alexander Loch MBBS, MRCP, MCEM, MD (SAGE Publishing, 2023)
Introduction: Ventricular remodeling is a mal-adaptive process. Both angiotensin-converting enzyme inhibitors and sacubitril/valsartan have been shown to reverse remodeling in mostly uncontrolled observational studies. There is a lack of head-to-head studies. Methods: This cohort study compares the remodeling effects of angiotensin receptor blockers combined with a neprilysin inhibitor (ARNI) and perindopril in heart failure with reduced ejection fraction (HFrEF) patients between January 2017 and December 2020. Inclusion criteria: (i) age > 18 years, (ii) recent diagnosis of de-novo HFrEF (EF < 40%), (iii) baseline echocardiography performed not more than 2 months prior to treatment onset, and (iv) follow-up echocardiography performed not earlier than 6 months and not later than 18 months posttreatment onset. No prior treatment with renin-angiotensin-aldosterone system inhibitors was permitted in the ARNI group. Left ventricular ejection fraction (LVEF), left ventricular end-diastolic volume (LVEDV), and left ventricular end-systolic volume (LVESV) were analyzed. A two-way repeated measure ANOVA (for normally distributed) and generalized estimating equation test for nonnormally distributed interval dependent variables. Mean comparison between and within groups was performed using the Bonferroni test. Results: Following an average treatment period of 9 months, LVEF improved from 24.9% to 36.4% for ARNI and from 28.7% to 40.5% for perindopril, increments of 11.5% and 11.8% resp. (Bonferroni test [ P  ≤ .05]). LVEDV was reduced by 8.4 mL and 3.2 mL, and LVESV by 17.9 mL and 10.8 mL for ARNI and perindopril resp. Only the reduction of LVESV for ARNI was statistically significant ( P  = .007). Conclusion: Both ARNI and perindopril yielded a significant improvement in the LVEF within 9 months. The remodeling effect of ARNI seems stronger because of the greater improvements in left ventricular volumes.